Diaphragm Activation in Ventilated Patients Using a Novel Transvenous Phrenic Nerve Pacing Catheter. Issue 7 (July 2017) - Reynolds, Steven; Ebner, Adrian; Meffen, Tracy; Thakkar, Viral; Gani, Matt; Taylor, Kaity; Clark, Linda; Sadarangani, Gautam; Meyyappan, Ramasamy; Sandoval, Rodrigo; Rohrs, Elizabeth; Hoffer, Joaquín A.
Abstract : Objectives: Over 30% of critically ill patients on positive-pressure mechanical ventilation have difficulty weaning from the ventilator, many of whom acquire ventilator-induced diaphragm dysfunction. Temporary transvenous phrenic nerve pacing using a novel electrode-bearing catheter may provide a means to prevent diaphragm atrophy, to strengthen an atrophied diaphragm, and mitigate the harms of mechanical ventilation. We tested the initial safety, feasibility, and impact on ventilation of this novel approach. Design: First-in-Humans case series. Setting: Angiogram suite. Patients: Twenty-four sedated, mechanically ventilated patients immediately prior to an elective atrial septal defect repair procedure. Interventions: A 9.5-Fr central venous catheter with 19 embedded electrodes was placed via Seldinger technique into the left subclavian vein and superior vena cava and evaluated for up to 90 minutes. The electrode combinations determined to provide best transvenous stimulation of the right and left phrenic nerves were activated in synchrony with mechanically ventilated breaths. Measurements and Main Results: One patient could not be tested for reasons unrelated to the device. In the 23 patients who underwent the full protocol, transvenous stimulation activated the diaphragm in 22 of 23 (96%) left phrenic capture attempts and 20 of 23 (87%) right phrenic capture attempts. In one subject, a congenital left-sided superior vena cava precluded right-sided capture. Significant reductions in ventilator pressure-time-product were achieved during stimulation assisted breaths in all 22 paced subjects (range, 9.9–48.6%; p < 0.001). There were no adverse events either immediately or at 2-week follow-up. Conclusions: In this First-in-Human series, diaphragm pacing with a temporary catheter was safe and effectively contributed to ventilation in conjunction with a mechanical ventilator. Abstract : Supplemental Digital Content is available in the text.